Consumer response to marketing channels: A demand-based approach. Issue 1 (2nd January 2020) - Andersen, Peter; Weisstein, Fei L.; Song, Lei
Abstract: Marketing channels have faced rapid structural and functional transformations during the last few decades. While a large body of research has been devoted to understanding the supply-side aspects of marketing channels, much less research has taken the demand-side perspective to study consumer perception of channel position and functions. This article extends the channel literature to a broader domain and develops a consumer-based theoretical framework reflecting factors that influence consumer perception of and reaction to channel strategies and decisions. The authors conceptualize that consumers' perceived channel value is a critical factor in determining their loyalty behavior. Seven important channel features are identified that would positively influence the perceived channel value. The relationship between perceived channel value and channel preference is strongly dependent on the level of customer value co-creation. The article concludes with research implications and suggestions of avenues for future research.